Aniline [MAK Value Documentation, 2018]. Issue 1 (30th January 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the workplace (MAK value) for aniline [62‐53‐3 ]. Available publications and unpublished study reports are described in detail. Healthy male and female volunteers showed increased methaemoglobin values in a 6‐hour‐inhalation‐study with exposure to 2 ml aniline/m 3 . The median methaemoglobin augmentation was 0.5% from the base level of 0.7% to 1.2% methaemoglobin. Even taking into account the highest observed increase of methaemoglobin, 8 hour‐exposure time and the increased respiratory volume at the workplace, a methaemoglobin value of more than 5% would not be expected. Based on this, the MAK value for aniline of 2 ml/m 3 (7.7 mg/m 3 ) is confirmed. Aniline is still assigned to Peak Limitation Category II, because systemic effects are critical and the excursion factor of 2 is confirmed. Skin contact is expected to contribute significantly to the systemic toxicity. Therefore, the designation with an "H" is confirmed. Aniline continues to be designated with "Sh" and assigned to Carcinogenicity Category 4.